Drinking Water Consumption in Cracow – an Assessment from a Sustainable Development Perspective - Stypka, Tomasz; Berbeka, Katarzyna (Problemy Ekorozwoju, 2014)
The article assesses, from a sustainable development perspective, the current consumption model for drinking water in Krakow. Based on the available literature, it evaluates the quality of tap water in Krakow and compares it with the standards for bottled water. Next it assesses the economic consequences for the average city resident who decides to drink bottled water. The total energy demand for the production, distribution and consumption of bottled water is estimated and is compared to the household energy consumption. The environmental impact for the current water consumption model in Krakow is estimated by summing the waste reaching landfills, energy consumption, carbon dioxide emission, and Eco-Indicator 99 H/A points. These estimates were calculated based on the data in the reviewed literature revised for the actual quantities of consumed bottled water and bottle recycling levels in Krakow. The potential environmental savings for the city related to an annual reduction of 1 litre of bottled water consumed by an average resident by is also calculated. The different water consumption scenarios are assessed using the multi-criteria Analytic Hierarchy Process (AHP) to see how compliant they are with sustainable development.